UPAYA KONSERVASI RUMAH ADAT KARO DALAM MENUNJANG PARIWISATA BUDAYA DI DESA LINGGA KABUPATEN KARO SUMATERA UTARA - Rikka Agustriana Sinulingga; I Gst. Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2016)
Karo traditional house is the cultural heritage of the ancestors that should be preserved. Karo Traditional House or Rumah Siwaluh Jabu is a home stage which is about 2 meters off the ground and usually inhabited by eight to ten households. Karo Traditional House could still be found in some areas in Karo like Dokan, Melas, and Lingga. Nowadays, the existence of Karo traditional house especially in Linga is reduced, where in 2002 the number of Karo traditional house totaling 29 units and it is only two units now. The number of traditional house is no longer groomed and crumbling with age and due to the lack of attention from the local government and the community. In this study, the problems are how the efforts made by the government and the community in conserving the Karo traditional house in Lingga. The location of this study is conducted in the village named Lingga, Simpang Empat sub district, Karo District of North Sumatra. Data collection methods used in this study is observation, interviews, literature study. An attempt by the government in this case the Department of Tourism and Culture of Karo viewed of the strategy, work programs, targets and achievements that provide land to relocate the modern house, the maintenance of Karo traditional house, hosted a party of flowers and fruit, held cultural festival in Lingga. Meanwhile, from the community side, it could be seen from the management and packaging of travel packages.